MASALAH KARAKTER ANAK: STRATEGI DAN UPAYA MENGATASINYA - Yandri A. Silaban; Eigrace Y. Sormin; Damayanti Nababan (CV. Denasya Smart Publisher, 2024)
Christian character is a collection of values and behaviors that are based on the teachings of the Bible. Christian character is important for children to have, because it can help thembecome good and responsible individuals. The impact of the absence of Christian character on children in society can be in the form of: Inability to socialize well. Children who do not have Christian character tend to find it difficult to socialize well. They may become quiet, shy, or even aggressive. Deviant behavior. Children who do not have Christian character tend to more easily engage in deviant behavior, such as lying, theft, or violence. Inability to face challenges. Children who do not have Christian character tend to give up more easily in the face of challenges. They may become pessimistic or even hopeless. Christian character is a collection of values and behavior based on the teachings of the Bible. Christian character is important for children to have, because it can help them become good and responsible individuals. The Bible teaches values such as love, forgiveness, honesty and justice. These values are important for children to have, because they can help them become individuals who: Have love and empathy for others, are able to forgive other people's mistakes, are honest and trustworthy, are able to act fairly and impartially, obey Christian character.